2018
DOI: 10.1002/tox.22621
|View full text |Cite
|
Sign up to set email alerts
|

Effects and mechanisms of betulinic acid on improving EGFR TKI‐resistance of lung cancer cells

Abstract: Epidermal growth factor receptor (EGFR) mutations have been identified in approximately 55% of lung cancer patients in Taiwan. Gefitinib (Iressa) and Erlotinib (Tarceva) are the first-generation targeting drugs to patients with EGFR gene mutants a work by inhibiting tyrosine kinase activity. However, resistance in EGFR-mutated patients to first-generation tyrosine kinase inhibitor (TKI) therapy after 8-11 months of treatment has occurred. Betulinic acid (BetA) is a pentacyclic triterpenoid natural product deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…The study showed that the combination of BA and TKIs increased cell death in HCC827 and H1975 lung cancer cell lines by increasing the expression of apoptotic proteins and autophagy. Combination therapy with these compounds improved the effectiveness of anti-cancer therapy and reduced the side effects of chemotherapeutic agents [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that the combination of BA and TKIs increased cell death in HCC827 and H1975 lung cancer cell lines by increasing the expression of apoptotic proteins and autophagy. Combination therapy with these compounds improved the effectiveness of anti-cancer therapy and reduced the side effects of chemotherapeutic agents [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…breast and lung cancer (Ko et al, 2018;Cai et al, 2018;Wang et al, 2019c) inhibiting metabolism CAV1, IKBA, LDHA/B, MYC, PDK1, RELA breast cancer (Jiao et al, 2019;Zeng et al, 2019) suppressing stemness NANOG, OCT4, PRKAA2, SOX2 pancreatic cancer (Sun et al, 2019) b-Sitosterol promoting apoptosis BAX, BCL2, CASP3 gastric cancer (Zhao et al, 2009) sensitizing chemotherapy AKT1, GSK3B, RELA, BAX, BCL2, SNAIL1, VIM pancreatic cancer (Cao et al, 2018) Triterpenes Lupeol anti-proliferation AKT1, BCL2, CCNA2/B/D3, CDC2/ 26C, CDK2/N1A/N1B/N2A, CLAUDIN1, CTNNB1, MAPK1, MYC, PLK1, TCF4, TP53…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…Akciğer adenokarsinoma hücre soylarında yapılan diğer bir çalışmada, akciğer kanserinde sıklıkla mutasyonu gözlenen endoteliyal büyüme faktörü reseptörünün (EGFR) tirozin kinaz inhibitörleri (TKI) Gefitinib ve Erlotinib'e dirençli H1975 ve EGFR mutant TKI duyarlı HCC827 hücre soylarında betülinik asidin, EGFR-TKI ile kombine tedavisi sonucu H1975 hücrelerinin canlılığını azalttığı, apoptotik hücre oranını arttırdığı ve hücre döngüsü ilişkili proteinlerin ekspresyonunu azalttığı gözlemlenmiştir. Ek olarak, otofaji ilişkili proteinlerin ekspresyonlarını arttırıp mitokondri membran potansiyelinin kaybına yol açmıştır (30). Son yıllarda ilaç etkinliğinin iyileştirilmesinde nanopartükül teknolojisi sıklıkla kullanılmaktadır.…”
Section: Ataş Ve Ergenunclassified